An Image Denoising-deblurring Adaptive Variational Problem in BV Space (Journal of Partial Differential Equations, 2020)
In this paper, we establish the existence and uniqueness of a BV solution to an initial boundary value problem for a nonlinear integro-differential equation, which is related to a denoising and deblurring variational model in image restoration. Several experiments relevant to the restoration model are performed and numerical results are discussed.
Keywords: Existence; uniqueness; BV solution; nonlinear integro-differential equation; image restoration